The Philosophy Of Madhzab Mu'tazilah And Asy'ariyah In Interpreting The Personality Of God: Rationalism In The Tradition Of The Kalam Philosophy - Fuad Noorzeha; Agus Sutono (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This article examines the concept of God's personality based on the perspectives of the Mu'tazilah and Asy'ariah, two Islamic theological schools with different approaches. The Mu'tazilah adopts a moderate framework grounded in rationalism, while the Asy'ariah employs a traditional classical framework emphasizing the theological intellectualism of Ahlussunnah wal Jama'ah. This study uses a literature review method with a historical textual approach to analyze the ideas of these two schools. The results show that the concept of God's personality, according to the Mu'tazilah, is formulated through the relationship between the Essence (Ijabiyah) and the inseparable attributes of God. Attributes such as Iradah (Will), Sama' (Hearing), Basr (Sight), and Kalam (Speech) are considered inherent to God's Essence. In contrast, the Asy'ariah does not separate God's attributes from His Essence, emphasizing that God does not consist of internal or external elements. Both schools share a common starting point in maintaining rationalism in monotheism, yet differ in their approaches to God's attributes. This article also highlights how both schools strive to distinguish God from the characteristics of created beings while maintaining a rational approach. This research contributes to academic discourse by enriching Islamic theological studies, particularly in understanding the role of rationalism in monotheism. It also provides an alternative perspective for rational theological understanding. Further research is recommended to explore the relevance of these concepts in contemporary theological discussions, including their connections to philosophy and interdisciplinary Islamic studies.